2022
DOI: 10.3389/fimmu.2022.974604
|View full text |Cite
|
Sign up to set email alerts
|

Genomics and transcriptomics reveal new molecular mechanism of vibriosis resistance in fish

Abstract: Infectious diseases have caused dramatic production decline and economic loss for fish aquaculture. However, the poor understanding of fish disease resistance severely hampered disease prevention. Chinese tongue sole (Cynoglossus semilaevis) is an important economic flatfish suffering from vibriosis. Here we used genomic, transcriptomic and experimental approaches to investigate the molecular genetic mechanisms underlying fish vibriosis resistance. A genome-wide comparison revealed that the genes under selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…We identified 713 genes exhibiting significant differences at the transcript level, of which some such as lyg, tlr4, sdf2, cxcr4, tacr3, and others were more highly expressed in the resistant family than in the susceptible family ( 24 ). For skin tissues, 1421 differentially expressed genes were identified and were significantly enriched in ECM-receptor interaction, complement and coagulation cascades, cardiac muscle contraction, starch and sucrose metabolism and aminoacyl-tRNA biosynthesis pathway ( 25 ). These findings indicated that multiple genes might control fish resistance against vibriosis.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 713 genes exhibiting significant differences at the transcript level, of which some such as lyg, tlr4, sdf2, cxcr4, tacr3, and others were more highly expressed in the resistant family than in the susceptible family ( 24 ). For skin tissues, 1421 differentially expressed genes were identified and were significantly enriched in ECM-receptor interaction, complement and coagulation cascades, cardiac muscle contraction, starch and sucrose metabolism and aminoacyl-tRNA biosynthesis pathway ( 25 ). These findings indicated that multiple genes might control fish resistance against vibriosis.…”
Section: Discussionmentioning
confidence: 99%